Optical Properties of Cadmium Oxide (CdO) Thin Films - Hadaate Ullah; Ridoanur Rahaman; Shahin Mahmud (Institute of Advanced Engineering and Science, 2017)
Cadmium (Cd) is a soft, silver-white or blue lustrous metal typically found in mineral deposits with lead, zinc and copper. Cadmium Oxide thin films have been prepared on a glass substrate at 3500C temperature by implementing the Spray Pyrolysis method. The direct and indirect band gap energies are determined using spectral data. The direct and indirect band gap energies decrease with the increasing film thickness. It is noted that for the same film thickness the direct band gap energy is greater than indirect band gap energy. The transmittance increases with the increasing wavelength for annealed and deposited films. It is also noted that for the same wavelength the transmittance for deposited films is greater than the transmittance for annealed films.